Kepatuhan Kebersihan Tangan Perawat dalam Pelaksanaan Tindakan Keperawatan di Ruang Rawat Inap Rumah Sakit - Andi Baso Tombong; Maesar Prayuda (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2025)
Hand hygiene compliance is a fundamental aspect of nursing practice and plays a critical role in preventing healthcare-associated infections (HAIs). Though literature highlight the importance of hand hygiene compliance, previous studies have not analyzed hand hygiene compliance based on nursing intervention type, especially in Indonesia. This study aims to assess the level of hand hygiene compliance among nurses at a hospital in South Sulawesi Province, based on nursing procedures outlined in the Ministry of Health Regulation No. 04 of 2022 on Technical Guidelines for Nursing Functional Positions. A descriptive quantitative design with an observational approach was employed. The study involved 57 nurses selected through quota sampling. Data were collected using a WHO-adapted hand hygiene observation sheet, documenting hand hygiene opportunities and corresponding nursing actions across three shifts: morning, afternoon, and night. Descriptive statistics, including frequencies and percentages, were used for analysis. Findings revealed that overall hand hygiene compliance among nurses was 61.30%, falling below the WHO standard of ≥85%. Notably, compliance was highest during wound care procedures, with rates ranging from 58.33% to 100%. However, adherence remained inconsistent across other nursing actions. The study concludes that while hand hygiene compliance is relatively high during wound care, consistent adherence should have been implemented across all nursing activities. This adherence aims to minimize infection risks, enhance patient safety, and ensure the delivery of high-quality nursing care.